Formulation, development, and in vitro evaluation of a nanoliposomal delivery system for mebendazole and gefitinib - Maram Kutkut, Ashok K. Shakya, Hamdi Nsairat, Mohamed El-Tanani (Journal of Applied Pharmaceutical Science, 2023)
Gefitinib (GEF) is the first-line therapy for lung cancer. Mebendazole (MBZ) is a synthetic antiparasite drug with reported cytotoxicity against lung cancer through Ran GTPase inhibition. Ran, a small G-protein, plays a vital role in cell growth. Since GEF therapy usually exhibits resistance and due to the low aqueous solubility of MBZ, this study was designed to investigate the anti-cancer effect of MBZ and GEF nanoliposomal formation compared to free MBZ and GEF, and the liposomal combination of the two drugs against lung cancer. The nanoliposomes were prepared using the thin-film hydration extrusion method and were fully characterized for their zeta sizer measurements and further investigated for their in vitro cytotoxicity and migration effects against A549 cell lines. The prepared nanoliposomes showed an average particle size of 176.52 ± 8.98 and 188.32 ± 5.28 nm with a zeta potential of −17.00 ± 0.15 and −17.16 ± 0.25 for MBZ and GEF, respectively, and a polydispersity index less than 0.2, indicating high stability over a 1-month period. MBZ and GEF had encapsulation efficiencies of 38.70% ± 1.98% and 55.06% ±1.98%, respectively. MBZ liposomes, GEF liposomes, and a liposomal mixture of both drugs had IC50 values of 283.4, 201.9, and 169.39 nM, respectively, after 72 hours, and demonstrated cytotoxic efficacy better than free drugs. In this study, MBZ and GEF were loaded into nanoliposomes with cytotoxicity that could make GEF more sensitive to A549 cell lines.